2012
DOI: 10.1007/s10571-012-9799-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxytocin on Neuroblastoma Cell Viability and Growth

Abstract: Oxytocin, released in response to different physiological stimuli, could play a key role in reducing stress reaction. It was suggested that it has protective effect against inflammation and consequences of oxidative stress. Mechanisms how oxytocin effects mediated in the brain tissue are unclear. In this study, oxytocin effect on cell growth and neuronal viability was examined. Human neuroblastoma (SH-SY5Y and SK-N-SH) and glioblastoma (U87MG) cells were exposed to different concentrations of oxytocin for 12-9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 27 publications
1
17
0
2
Order By: Relevance
“…The SH-SY5Y neurons express oxytocin receptors [32] and oxytocin has neuroprotective actions in this cell line [33]. The effects of atosiban, an antagonist of oxytocin [34], on KiSS-1 overexpression neuroprotection against A β were therefore tested at a dose (1  μ M) that is known to be effective in cell culture models.…”
Section: Resultsmentioning
confidence: 99%
“…The SH-SY5Y neurons express oxytocin receptors [32] and oxytocin has neuroprotective actions in this cell line [33]. The effects of atosiban, an antagonist of oxytocin [34], on KiSS-1 overexpression neuroprotection against A β were therefore tested at a dose (1  μ M) that is known to be effective in cell culture models.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, oxytocin shows slight neuroprotective effect by increasing the antioxidant capacity and stabilized oxidant status in comparison with NB cells. Bakos J and colleagues' [4] studies show 0.01-1 μM oxytocin increases neuroblastoma viability against hydrogen peroxide toxicity. Although they showed an icrease in viability, they did not report increases in neurotrophic factor levels.…”
Section: Discussionmentioning
confidence: 96%
“…OT receptors are present in the central nervous system and participates in both basic physiology and cancer pathophysiology. It was shown in brain membranes that OT has antioxidant properties, scavenging free peroxyl radicals, inhibiting LDL oxidation and lipid peroxidation [4]. Current study was designed to investigate the possible protective effect of OT against VCR and CP-induced neurotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, many studies, both in vitro and in vivo, have suggested the cytoprotective and trophic potential of oxytocin using various experimental models (Iseri et al 2005;Ceanga et al 2010;Alizadeh et al 2012;Bakos et al 2012;Erbas et al 2012b;Leuner et al 2012). For instance, preincubation of cells with OT reduces toxicity and induce cell viability in neuronal cell cultures exposed to 6-OHDA (Bakos et al 2012). Recently, we have demonstrated the beneficial effect of OT against sepsis-induced polyneuropathy by evaluating electromyography (EMG) changes and biochemical parameters including plasma TNF-α, malondialdehyde and total anti-oxidant capacity in critical illness (Erbas et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it elicits anti-inflammatory and anti-oxidant effects in ischemia-reperfusion injury and sepsis-induced multiple organ damage via maintaining a balance of antiinflammatory and pro-inflammatory cytokines (Iseri et al 2005;Alizadeh et al 2012). Recently, in vitro and in vivo studies have suggested the stimulatory effect of OT on cell viability against neuronal cell death (Bakos et al 2012;Leuner et al 2012).…”
Section: Introductionmentioning
confidence: 99%